A Look into the Tiny Flat Plates Sheathing the Flimsy Wings of Amata Passalis using Light Microscopy (Global Journal of Science Frontier Research, 2020)
Amata passalis is a moth popularlyknown assandal wood defoliator, belonging to the family Erebidae under the order lepidoptera. The framework of this study mainly concentrates on the different types of scale cells present on the varied coloured wing areas. The study has been conducted experimentally by scrapping off different coloured scales to a glass slide and fixing it with xylene and observing it under a light microscope. The dimensions of the scales were also studied by measuring it using micrometry. A total of 68 morphologically distincttypes of scales were studied, which includes 48 scales of the dorsal wing and 20 scales of the ventral wing. Analysis of both the dorsal and ventral wing areas revealed the presence of several white, brown and and grey coloured scales. This moth species posess a wing pattern with black coloured region surfaced by white spots. Black and white scales cannot be extracted separately, as the sclaes seen on the white spotted region are small sized ones. Majority of the scales of the dorsal region were point edgedones and they have a length range of about 110.3µm to 149.7µm and width range of 59.1µm to 78.5µm. While examining the ventral wing it was observed that majority of the scales were heart shaped ones.
Keywords: flimsy wings; light microscopy; micrometry; moth; flat plates